HETEROSIS PADA SEMANGKA (Citrullus vulgaris, Schard.) DENGAN TETUA BETINA JANTAN MANDUL TRIPLOID DAN TETUA JANTAN SEMANGKA DIPLOID - Sutikno, Agus (Universitas Islam Darul Ulum, 2009)
Seedless watermelon is promising commodity. Some breeding program are, therefore, needed to obtain prime progeny of crossing. The use of suitable pollinators can improve agronomic traits like sugar level, fruitâs diameter, fruitâs length, etc. To obtain desired information, a field research was conducted using Plot Random Design with two replications of two triploid and nine diploid watermelons and they were combined to get thirty-six combinations. The analysis used to support the information was Analysis of Variance, and Duncanâs Test. The information obtained was that good results are found on agronomic traits of sugar level and fruitâs diameter. Fruitâs diameter were satisfying in the crossing between Pretty Orchid (V1) and Grand Master (P7), and TM Tiger (P8) and China Dragon (P3), sized 21,49 cm and 20,21 cm, respectively.Â